Numerical simulation of particle spatial distribution and filtration characteristic in the pleated filter media using OpenFOAM. Issue 8 (October 2021) - Shu, Zhiyong; Qian, Fuping; Fang, Can; Zhu, Jingjing
Fine dust is one of the important factors affecting precision instruments and human health, and the pleated filter media has been widely used in air filtration field. Based on the SEM image of the actual pleated filter media, a microscopic 3D model of the pleated filter media was established and the gas–solid two-phase flow was simulated using OpenFOAM. The results show that OpenFOAM can well simulate the particle deposition on the surface of the fibre filter media and the dendritic structures. The transverse distribution of the amount of deposited particle in the pleated filter media is in the form of two peaks structure, while the longitudinal distributions of the amount of deposited particle in 30° and 60° of the pleated filter media are relatively uniform with multi-peaks structure. The average relative error of the pressure drop between the simulation result and the empirical formula is 3.69%, and the pressure differential decreases first and then increases with the pleated angle, and at a gas velocity of 0.4 m/s, Δ P min is around 5 Pa (35° of the pleated angle). Through the above studies, the results could be helpful for the development and design of the pleated filter media.